(untitled) (Global Journal of Management and Business Research, 2015)
Ethics, an essential dimension of human research, is considered both as discipline and practice. For clinical research, ethically justified criteria for the design, conduct, and review of clinical investigation can be identified by obligations to both the researcher and human subject. Medical practitioners are expected to not only have the skills and knowledge relevant to their field but also with the ethical and legal expectations that arise out of the standard practices. A highest level of knowledge, awareness and understanding of ethics are expected in medical practice as it is the foundation of sound healthcare delivery system. Though literatures review, status quos of medical evaluation system are found in China. Although Chinese government attach extreme important to ethics evaluation, medical ethics education and building can be value by China. Negative List System is used in health management field firstly. Some suggestions are given to government to improve development of medical ethics evaluation system.